Pengaruh PENGARUH JUMLAH KOMISARIS INDEPENDEN PADA NILAI PERUSAHAAN DENGAN EFISIENSI PERUSAHAAN SEBAGAI VARIABEL MODERASI: STUDI PADA SEKTOR PERBANKAN DI INDONESIA - Prawirosaputro, Bima; Bimo, Irenius Dwinanto (Jurnal Manajemen, 2025)
This study aims to analyze the influence of the number of independent commissioners on company profitability with operational efficiency as a moderating variable. The study focuses on the banking sector in Indonesia listed on the Indonesia Stock Exchange for the years 2016-2020. The sample analyzed consists of 37 banks with 167 observations over 5 years. This study conducted hypothesis testing through panel data regression analysis processed using the STATA 17 statistical program. From the panel data regression analysis results, it can be concluded that the number of independent commissioners significantly positively impacts company profitability. It was also found that operational efficiency significantly moderates the relationship between the number of independent commissioners and company profitability.